Variations in Morphologial Changes of Indonesian Words on Instagram Accounts (Morphological Studies) - Nasibah Sholehah; Ratna Juwitasari Emha (PIKTORIAL : Journal of Humanities, 2022)
The study aims to describe the form of morphological changes of words in Indonesian on instagram accounts and the pattern of their formation. This research method is qualitavive, in this study it is intended to understand how the form of morphological changes in indonesian and how these patterns shape especially in instagram social media where there are efforts to explain, record, analyze, and understan various kinds of morphological changes. Data collection techniques in this study used reading, note-taking, and screenshot techniques. The source of data in this study is a short description contained in posts on instagram accounts as well as image posts containing words. The results of this study show that the Indonesian language in the Instagram account undergoes 4 morphological changes, each of which shows a distinctive pattern characteristic morphological changes (1) affixation has 3 patterns, namely Indonesian prefix plus English root, English root plus Indonesian suffix, Indonesian confix plus Indonesian root, (2) Indonesian reduplication, complete Indonesian repetition, the patterns are, repetition of Indonesian plus changes in Indonesian, (3) composition of Indonesian, pattern combining compound words plus changes in Indonesian meaning, (4) acronyms of Indonesian , the pattern of shortening Indonesian words plus changes in Indonesia.